The Evolution of the Field of Biomechanics Through the Lens of Experimental Mechanics - Xu, S.; Grande-Allen, K. J. (Experimental mechanics, 2010)
Biomechanics is a young field that entails the study of the mechanical aspects of the life and health sciences. The growth of this field can be attributed to the growth of cutting-edge technologies that enable scientists to investigate the mechanics of life with increasing acuity. Founded in 1961, the journal Experimental Mechanics (EM) has had an important role in the growth and scholarship of the field of biomechanics. From the mid-1960’s to mid-1970’s, relevant publications in EM focused on characterizing potential bioimplants and exploring the mechanical properties of connective tissues. The next two decades witnessed a clear drop in biomechanics papers in EM, perhaps due to the rise of biomechanics-specific societies and journals that offered a more dedicated audience while EM sought a more varied readership. More recently, there has been a resurgence of biomechanics publications in EM, including 3 recent special issues devoted to the subject. The journal has brought forth an impressive range of biomechanics related papers including cellular and nanoscale studies, characterization of biological tissues and novel biomaterials, and most importantly, the development of novel technologies and devices that are applicable across the entire field. Digital image correlation and digital volume correlation are examples of techniques presented in EM that have been applied to numerous biomechanics problems. Although the field has exhibited exponential growth in the past 15 years, a myriad of scientific questions, especially on the cellular and subcellular level, remain to be answered. EM should cultivate its future role in shaping this exciting field.